2014
DOI: 10.4314/tjpr.v13i1.16
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Sub-Acute Toxicity of Aqueous Extract of <i>Nauclea Latifolia</i> in Swiss Mice and in OFA Rats

Abstract: Purpose: To determine the dose -toxicity profile of the aqueous extract of Nauclea latifolia stem bark (AQE). Methods:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
9
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 15 publications
(23 reference statements)
5
9
1
Order By: Relevance
“…Probably this might be due to high rate of recovery of blood cells from the effect of VPA. This do not corroborate the study of Kouadio et al [30] who reported elevation of platelets, erythrocytes and eosinophils reflecting potential benefits in blood coagulation, anemia and allergenic effect respectively. Valproic acid in previous studies has been shown to cause coagulopathy, platelet dysfunction and thrombocytopenia thought to be associated with possibly direct toxicity on bone marrow or VPA inclusion into platelet membrane due to similar fatty acid cell membranes [51].…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Probably this might be due to high rate of recovery of blood cells from the effect of VPA. This do not corroborate the study of Kouadio et al [30] who reported elevation of platelets, erythrocytes and eosinophils reflecting potential benefits in blood coagulation, anemia and allergenic effect respectively. Valproic acid in previous studies has been shown to cause coagulopathy, platelet dysfunction and thrombocytopenia thought to be associated with possibly direct toxicity on bone marrow or VPA inclusion into platelet membrane due to similar fatty acid cell membranes [51].…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, there was steady weight gain (P < 0.001) during the treatment period. This indicates the absence of weight related adverse effect and possible improvement in nutritional status [30]. Previous study by Kouadio et al [30], also demonstrated significant weight gain in rats administered the aqueous stem -bark extract of Nauclea latifolia.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations